The Pragmatic Dimensions at Ibn Hazm Al Andalusi - Al-Alawi, Majid bin Hamad (Journal of Humanities & Social Sciences, 2018)
We start this study with the following question: Does commitment to the linguistic manifestation necessarily mean to be satisfied with linguistic structure and the exclusion of pragmatic data in understanding the text? The answer to the previous question prompts us to adopt a hypothesis, to choose a traditional personality, and to determine the pragmatic dimensions of the thought of this personality through his text applications. This is available according to the opinion of this study through the search for the hypothesis of the existence of the pragmatic dimensions in the most prominent extrinsic personality in the Arab and Islamic heritage. It is common among a number of researchers that the virtual school ,and on their head, Ibn Hazm Al Andalusi (died in 456 Hijri) do not rely on the used data , but most of their textual practices depend on linguistic structures and are not separated .Thus, this study is directed to reveal the pragmatic dimensions that comes out of the linguistic structures in the applied practices of Ibn Hazem from the pragmatic linguistic performed perspective . The point that should be made clear here is that the combination of syntax and pragmatics suggests some difficulty at the beginning. However, contemporary linguistic studies have settled this matter . There are different studies and research interests in the fields of linguistics and pragmatics. The abstract sentence is considered as one of the linguistics interests since Ferdinand de Saussre including the structuralists linguists. The studies of linguistics have worked on studying the language itself for its own sake in order to exclude what can influence the objectivity of language studies and their science. However, the pragmatic linguistics came out of this criterion to re-consider the non-linguistic factors, including the situation, context and external clues. Therefore, the manifestations of the sentence in the communicative situations have become one of the achievements of Pragmatics. And therefore we are in front of a conceptual system that can derive its tools of linguistics and pragmatics in its contextual andargumentative dimensions according to the theory of acts of speech.